ATR-FTIR characterization of generic brand-named and counterfeit sildenafil- and tadalafil-based tablets found on the Brazilian market. Issue 4 (July 2017) - Coelho Neto, José; Lisboa, Fernanda L.C.
Abstract: Viagra and Cialis are among the most counterfeited medicines in many parts of the world, including Brazil. Despite the many studies that have been made regarding discrimination between genuine and counterfeit samples, most published works do not contemplate generic and similar versions of these medicines and also do not explore excipients/adjuvants contributions when characterizing genuine and suspected samples. In this study, we present our findings in exploring ATR-FTIR spectral profiles for characterizing both genuine and questioned samples of several generic and brand-name sildenafil- and tadalafil-based tablets available on the Brazilian market, including Viagra and Cialis. Multi-component spectral matching (deconvolution), objective visual comparison and correlation tests were used during analysis. Besides from allowing simple and quick identification of counterfeits, results obtained evidenced the strong spectral similarities between generic and brand-named tablets employing the same active ingredient and the indistinguishability between samples produced by the same manufacturer, generic or not. For all sildenafil-based and some tadalafil-based tablets tested, differentiation between samples from different manufacturers, attributed to slight variations in excipients/adjuvants proportions, was achieved, thus allowing the possibility of tracing an unknown/unidentified tablet back to a specific manufacturer. Highlights: Identification of active ingredient and major excipients present on each sample Samples from different manufacturers can be distinguished on most cases. Samples from same manufacturer are indistinguishable. Easy identification of counterfeit samples Unknown/unidentified samples can be traced back to possible manufacturers.